Influence of earthworms on the microbial properties and extracellular enzyme activities during vermicomposting of raw and distilled grape marc. (1st October 2022) - Gómez-Brandón, María; Fornasier, Flavio; de Andrade, Nariane; Domínguez, Jorge
Abstract: The treatment of winery wastes by using appropriate management technologies is of utmost need in order to reduce to a minimum their disposal and avoid negative environmental impacts. This is of particular interest for grape marc, the main solid by-product of the winery industry. However, comparative studies on a pilot-scale dealing with the impact of earthworms on marc derived from both red and white grape varieties during vermicomposting are still scarce. The present study sought to evaluate the changes in the biochemical and microbiological properties of red and white raw marc in the presence and the absence of the earthworm species Eisenia andrei . The distilled marc obtained through distillation of the red grape marc was also considered under this scenario. Samples were taken after 14, 28, 42, and 63 days of vermicomposting. On day 14 earthworms led to a pronounced increase in most of the enzymatic activities, but only in those vermireactors fed with raw marc from the red grape variety. Alfa- and beta-glucosidase as well as chitinase and leucine-aminopeptidase activities were between 3 to 5-times higher relative to the control, while alkaline phosphomonoesterase was even up to 14-fold higher with earthworm presence. From day 28 onwards the magnitude of earthworms' effect on the studied enzymes was also dependent on the type of grape marc. Reduced values of basal respiration, ranging between 200 and 350 mg CO2 kg OM h −1 and indicative of stabilized materials were found in the resulting vermicomposts. Moreover, the content of macro- and micronutrients in the end products matched with those considered to have the quality criteria of a good vermicompost. Altogether, these findings reinforce the effectiveness of vermicomposting for the biological stabilization of grape marc with the dual purpose of fertilizer production and environmental protection. Highlights: The impact of Eisenia andrei was evaluated on raw and distilled marc over 63 days. Grape marc from white and red grape varieties was used as starting material. Earthworms' influence on extracellular enzyme activities was time-dependent. Red raw marc enzyme activities were up to 5- times higher on 14-day vermireactors. Stable vermicomposts had respiration values of 300 mg CO2 kg OM h −1 after 63 days.